Penerapan Model Pembelajaran Student Team Achievement Division (STAD) pada Pembelajaran IPS Siswa - Witra, Witra; Prananosa, Ahmad Gawdy; Satria, Tio Gusti (IJOCE: Indonesia Journal of Civic Education, 2025)
This study aims to determine the completeness of the social studies learning outcomes of grade IV students of SD Negeri 25 Lubuklinggau in the 2024/2025 academic year after the Student Team Achievement Division (STAD) Learning Model was implemented in social studies learning for grade IV.A students of SD Negeri 25 Lubuklinggau significantly complete. The type of research used was experimental. The population in this study was all grade IV students of SD Negeri 25 Lubuklinggau totaling 47 students and the sample was class IV.A. Sampling was carried out using the Random Sampling Technique. The data collection technique used a multiple-choice test. The data obtained were analyzed using the z-test post-test value at a significance level of α = 0.05, obtained Zcount (3.49)> Ztable (1.64), the average social studies learning outcomes of students after the implementation of the Student Team Achievement Division (STAD) learning model was 77.71 and the percentage of students who had achieved learning completeness reached 82.60%   Keywords: Student Team Achievement Division (STAD) Model, IPS.